ANALISIS STANDAR PEMBIAYAAN DALAM MENINGKATKAN MUTU PENDIDIKAN DI SMAN 1 KLARI KARAWANG: Analysis of Standard Financing in Improving Education Quality at SMAN 1 Klari Karawang - Fadilah Nur Zikriyah; Dimo Aditia Nugroho; Fathiyah Azahra; Hinggil Permana (STAI Ma'had Aly Al-Hikam Malang, 2025)
This article aims to analyze the implementation of education financing at SMAN 1 Klari Karawang from a legal perspective and strategies for improving education quality through effective and efficient financing. It uses a qualitative approach and case study method with data collection techniques such as observation, interviews, and documentation. The results of the study show that the management of financing at SMAN 1 Klari is in accordance with the law, particularly Government Regulation No. 57 of 2021 and Minister of Education, Culture, Research, and Technology Regulation No. 18 of 2023. The evidence is that the Education Unit Operational Assistance (BOSP) funds are managed transparently through ARKAS (School Activity and Budget Plan Application), although various obstacles are still encountered, such as delays in fund distribution and budget constraints. Meanwhile, to improve the quality of education through funding standards, SMAN 1 Klari implements strategies for efficient use of internal assets, maintains the effectiveness of programs even though their quality is not optimal, and involves voluntary support from parents and the community. In conclusion, SMAN 1 Klari has implemented the principles of transparency, accountability, and participation in the management of education costs, which has ultimately become the key to improving the quality of education at the school. Artikel ini bertujuan menganalisis implementasi pembiayaan pendidikan di SMAN 1 Klari Karawang dari perspektif perundang-undangan serta strategi peningkatan mutu pendidikan melalui efektivitas dan efisiensi pembiayaan. Menggunakan pendekatan kualitatif dan jenis studi kasus dengan teknik pengumpulan data berupa observasi, wawancara dan dokumentasi. Hasil penelitian menunjukkan pengelolaan pembiayaan di SMAN 1 Klari sesuai dengan perundang-undangan, khususnya PP Nomor 57 Tahun 2021 dan Permendikbudristek Nomor 18 Tahun 2023. Buktinya adalah dana Bantuan Operasional Satuan Pendidikan (BOSP) dikelola secara transparan melalui ARKAS (Aplikasi Rencana Kegiatan dan Anggaran Sekolah), meskipun masih dijumpai berbagai kendala seperti keterlambatan penyaluran dana dan keterbatasan anggaran. Sedangkan untuk meningkatkan kualitas pendidikan melalui standar pembiayaan, SMAN 1 Klari menerapkan strategi efisiensi penggunaan aset internal, menjaga efektivitas program meski kualitasnya tidak maksimal, serta melibatkan dukungan sukarela dari orang tua dan masyarakat. Kesimpulannya, SMAN 1 Klari telah menerapkan prinsip transparan, akuntabel, dan partisipatif dalam pengelolaan biaya pendidikan, hingga akhirnya menjadi kunci peningkatan mutu pendidikan di sekolah tersebut. Kata Kunci : Pendidikan; Peningkatan Mutu; Sekolah Menengah Atas; Standar Pembiayaan.